Biology for matriculation - Lee, Soon Ching; Sudani Sudin; Nalini B; Jacqueline R.S (Oxford Fajar Sdn Bhd, 2019)
Biology for Matriculation Semester 2 Fifth Edition Updated is a comprehensive coursebook written for students studying Biology in local matriculation courses. This coursebook aims to stimulate students' interest in biology and help them gain a firm understanding of important principles and concepts in biology. In addition, it helps students prepare for their Biology examination.